2003
DOI: 10.1002/iroh.200310625
|View full text |Cite
|
Sign up to set email alerts
|

Zooplankton Distribution in Tropical Reservoirs, South China

Abstract: The zooplankton of 18 reservoirs of South China was investigated in 2000. 61 Rotifera species, 23 Cladoceras and 14 Copepodas were identified. The most frequent Rotifera genera were Keratella, Brachionus, Trichocerca, Diurella, Ascomorpha, Polyarthra, Ploesoma, Asplanchna, Pompholyx and Conochilus. Bosmina longirostris, Bosminopsis deitersi, Diaphanosoma birgei, D. brachyurum and Moina micrura were typical of Cladocera in the reservoirs. Phyllodiaptomus tunguidus, Neodiaptomus schmackeri and Mesocyclops leuc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…This could be explained by the combined effects of zooplankton physiological limitations and the low phytoplankton growth in winter. Compared with other eutrophic reservoirs in China (Lin et al, 2003), the Chl-a contents in the Xiaowan Reservoir during winter were still low (<1 µg L -1 ). Several authors reported that the rotifer were richest in the number of individuals in reservoir (Nogueira, 2001;Seda and Devetter, 2000).…”
Section: Discussionmentioning
confidence: 78%
“…This could be explained by the combined effects of zooplankton physiological limitations and the low phytoplankton growth in winter. Compared with other eutrophic reservoirs in China (Lin et al, 2003), the Chl-a contents in the Xiaowan Reservoir during winter were still low (<1 µg L -1 ). Several authors reported that the rotifer were richest in the number of individuals in reservoir (Nogueira, 2001;Seda and Devetter, 2000).…”
Section: Discussionmentioning
confidence: 78%
“…P. truncatum is reported as thermophilic specimen (Koste 1978), and its embryonic development occurs at high temperatures, and this period continues for a long time (Edmondson 1960). P. truncatum was reported from various areas in the world including; Russia (Telesh 1995), Canada (Swadling et al 2000), China (Lin et al 2003;Zhaou et al 2009 Kehayias et al 2008), and North America (Barbiero and Warren 2011), except Turkey which is located in Palearctic region. Also, it has been a subject of several studies (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…After these large-scale water blooms, the local government began to realize the seriousness of water pollution, and many significant decisions were made with an aim at water resources protection. Another two surveys of harmful Cyanobacteria and internal loading in the reservoir were completed in 2003-2004and 2007-2008(Han et al 2006, Han 2010.…”
Section: Discussionmentioning
confidence: 99%
“…In total, a minimum of 61 species of Rotifera, at least 23 species of Cladocera and 18 species of Copepoda have been identified in samples collected in summer and winter (Lin et al 2003). The majority of rotifer species are monogononts, and bdelloids are represented only by Rotaria spp.…”
Section: Zooplanktonmentioning
confidence: 99%